Effect of temperature on crystallite size of hydroxyapatite powders obtained by wet precipitation process - Néstor Méndez-Lozano; Miguel Apátiga-Castro; Karen M. Soto; Alejandro Manzano-Ramírez; Marco Zamora-Antuñano; Carlos Gonzalez-Gutierrez (Journal of Saudi Chemical Society, 2022)
In this investigation, HAp powders were synthesized using the wet chemical precipitation technique. The temperature of the heat treatment (80 °C, 120 °C, and 160 °C) and the addition of glutamic acid were the considered process parameters. After the reaction between the precursors calcium nitrate [Ca(NO3)2] and ammonium phosphate [(NH4)H2PO4], decantation of the residue, drying, and finally, heat treatment of the residue were done sequentially. X-ray diffraction (XRD) analysis, scanning electron microscope (SEM) observations, and X-ray fluorescence (XRF) analysis were carried out to characterize the synthesized HAp powders. It was found that at a high heat treatment temperature plus the addition of glutamic acid are suitable process parameters to acquire uniform HAp powders with plate morphology and fibers with an average particle size of ∼100–200 µm. The Ca/P ratio obtained was like the hydroxyapatite present in the bones in the order of 1.72. This situation can be indicated as an essential advantage in the biocompatibility of the synthesized material. The use of glutamic acid suggests crystal growth in a preferential direction as reported in our previous work. The manufacture of hydroxyapatite, especially in powder, is of great interest in developing additive manufacturing systems for the biomedical market.